Efficacy of Pharmacotherapy for Smoking Cessation in Adolescent Smokers: A Meta-analysis of Randomized Controlled Trials. Issue 11 (28th August 2018) - Myung, Seung-Kwon; Park, Joo-Young
Abstract: Introduction: This study aimed to evaluate the efficacy of pharmacotherapy for smoking cessation among adolescent smokers by using a meta-analysis of randomized controlled trials (RCTs). Methods: PubMed, EMBASE, and Cochrane Library were searched from the inception to January 20, 2018. We included RCTs of pharmacotherapy for smoking cessation among adolescent smokers aged less than 20 years. Data were pooled using a random-effects meta-analysis. The primary outcome measures were a smoking abstinence rate and its relative risk (RR) at the longest follow-up period in each study validated by biochemical markers. Results: Among a total of 1035 articles searched, nine RCTs, which involved 1188 adolescent smokers aged 12–20 years with 627 in the intervention group and 561 in the control group, were included in the final analysis. In the random-effects meta-analysis of all the nine trials, pharmacotherapy showed a increased abstinence rate (RR = 1.62; 95% confidence interval [CI] = 1.08 to 2.44, I 2 = 0.0%), compared with the control group. Subgroup meta-analyses by follow-up period showed an increased abstinence rate at 4 weeks (RR = 1.87; 95% CI = 1.22 to 2.87; n = 4) and a nonsignificantly increased abstinence rate during the longer term follow-up periods at 8, 12, 24, and 52 weeks. Conclusions: The current meta-analysis suggests that pharmacotherapy can be considered as an aid for smoking cessation in the short-term period among adolescent smokers. However, further large RCTs are warranted to determine its long-term efficacy and safety. Implications: In this meta-analysis of nine RCTs with 1188 adolescent smokers aged 12–20 years, pharmacotherapy showed an increased abstinence rate, compared with the control group. In the subgroup meta-analyses by follow-up period, it showed the increased abstinence rate at 4 weeks and no efficacy on abstinence during the longer term follow-up periods up to 52 weeks. Further large RCTs are warranted to determine the long-term efficacy and safety of pharmacotherapy in adolescent smokers.